Hospital costs associated with adverse drug events: Systematic review (Research, Society and Development, 2021)
Context: Adverse drug events (AMEs) are among the most routine causes during the care process in the hospital environment. It is characterized as any unfavorable clinical occurrence that may affect the patient during the treatment period and is not attributed to the natural evolution of the underlying disease. Objective: To analyze the costs of care provided to patients affected by AMEs. Methodology: Systematic review with writing based on the PRISMA checklist and Meta-analysis of Observational Studies in Epidemiology Statements (MOOSE) with consultation in the PubMed, Embase, Cochrane and LILACS literature databases in February 2020. The studies were selected from the controlled descriptors and their synonyms: “Drug-Related Side Effects and Adverse Reactions” and “Hospital Costs” and for the English version, Mesh was used. The risk of bias was analyzed using the Newcastle-Ottawa tool. Results: The analysis included eight studies and showed that there is an intense increase in costs associated with the occurrence of AMI, as well as negative consequences such as increased length of hospital stay, the need for specialized labor and exposure to patient damage. Conclusions: This analysis can be a powerful managerial tool for health institutions as a demonstration of the costs arising from the AMS, as well as providing subsidies for future research.